Microvascular Angiopathic Consequences of COVID-19 - Nalugo, Margaret; Schulte, Linda J.; Masood, Muhammad F.; Zayed, Mohamed A. (Frontiers in Cardiovascular Medicine, 2021)
The coronavirus disease-2019 (COVID-19) pandemic has rapidly spread across the world. The disease is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which first appeared in Wuhan, China in December, 2019. Ever increasing data is continuing to emerge about the impact of COVID-19 on cardiovascular tissue and other organ system. Clinical features associated with COVID-19 suggest that endothelial cell dysfunction and microvascular thrombosis are to a large extent contributing to resultant multi-organ complications. This review is aimed at highlighting the critical aspects associated with COVID-19 and its presumed microvascular angiopathic consequences on the cardiovascular system leading to multi-organ dysfunction.